Transumbilical glove port: A cost-effective method for single-incision laparoscopic hepatectomy - Ryohei Miyata; Noriaki Kameyama; Masato Tomita; Hiroaki Mitsuhashi; Shigeaki Baba; Ryusuke Amemiya; En Amada (SAGE Open Medical Case Reports, 2015)
Objectives: Emerging concepts of “reduced port surgery” have gained considerable attention from laparoscopic surgeons, including the field of liver resection. To date, 86 cases of single-incision laparoscopic hepatectomy (SILH) have been reported, with commercially available access devices being used in most of these cases. We report herein a use of homemade transumbilical glove port for SILH. Methods: A 39-year-old woman represented giant hepatic hemangioma (9-cm in size) located at the left lateral segment (S2/3). Partial hepatectomy was performed by the glove method via single port access with conventional laparoscopic bipolar forceps, grasper and scissors without the need of any single-port specific devices. Results: The operative time was 77 minutes, and intraoperative blood loss was 50 mL. The postoperative course was uneventful. Conclusions: Glove method not only has significant advantages in terms of cost, but also is superior in its versatility, allowing wider range of movements compared to conventional access devices. Taking in consideration its cost effectiveness and versatility, glove method may be a good option for SILH.